2015
DOI: 10.1177/0107408315599691
|View full text |Cite
|
Sign up to set email alerts
|

Identifying variables in relation to health-related quality of life among community-dwelling older women: Knowledgebase for health-promoting activities

Abstract: The aim of the present study was to explore health-related quality of life (HRQoL) and associated variables among all community-dwelling older women (565 years) (n ¼ 2724) on Å land, a Finnish self-governing island community. A total of 1023 women participated (mean age 72.9 AE 6.8 years). Absence of depression, absence of diagnosed disease(s), having the opportunity to engage in meaningful leisure activities, and never or seldom feeling lonely explained, together with socioeconomic control variables (i.e. age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Obviously, feeling lonely or expressing symptoms of depressive disorders is not per se the same as mental ill health. However, it is known that symptoms of depressive disorders, depression and loneliness are strongly associated with poor health and well-being and with each other (Bergdahl, Allard, Lundman, & Gustafson, 2007;Boman et al, 2015a;Cacioppo, Huges, Waite, Hawkley, & Thisted, 2006;Dahlberg, Andersson, McKee, & Lennartsson, 2015). Depression has also previously shown associations with weak inner strength (Boman et al, 2014;Viglund et al, 2014) Hildon, & Blane, 2008;Windle, Markland, & Woods, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, feeling lonely or expressing symptoms of depressive disorders is not per se the same as mental ill health. However, it is known that symptoms of depressive disorders, depression and loneliness are strongly associated with poor health and well-being and with each other (Bergdahl, Allard, Lundman, & Gustafson, 2007;Boman et al, 2015a;Cacioppo, Huges, Waite, Hawkley, & Thisted, 2006;Dahlberg, Andersson, McKee, & Lennartsson, 2015). Depression has also previously shown associations with weak inner strength (Boman et al, 2014;Viglund et al, 2014) Hildon, & Blane, 2008;Windle, Markland, & Woods, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is further indicated that inner strength partially mediates the relationship between disease and self‐rated health; more inner strength is associated with better self‐rated health (Viglund et al., ). In another study including only older women, strong inner strength is associated with better mental health, but not physical health (Boman, Häggblom, Lundman, Nygren, & Fischer, ). Furthermore, strong inner strength among older women is related to reduced prevalence of depression (Boman, Gustafson, Häggblom, Santamäki Fischer, & Nygren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies have shown that a higher degree of IS was associated with better health among older individuals, and that IS partly mediated the relationship between having a disease and self-rated health. 12,13 IS was positively related to physical and mental health, 14 to lack of signs of depression among older women, 15 and to physical and mental health among older individuals with chronic illnesses. 16…”
Section: Introductionmentioning
confidence: 88%
“…Based on the MIS, we developed the Inner Strength Scale (ISS), 21 which has hitherto been used in studies among older adults. 1215 The model has also been used as a theoretical framework in studies with a qualitative design. 7,22 In a study with a deductive approach among older women, IS was described as ‘It is all up to you’, ‘Strive to be in communion’, ‘Make the best of the situation’, and ‘A balancing act’.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been found that quality of care is related to QoL among older people receiving HCS [ 23 ]. Low QoL has been found to be associated with reduced ADL function, depression, loneliness, not being engaged in meaningful activities [ 6 , 24 , 25 ], social isolation [ 24 , 26 ] and pain [ 6 ]. However, it has also been shown that high quality care can compensate for the deficiencies mentioned above and result in an improved QoL [ 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%